Teaching Style Differences between Male and Female Science Teachers in Qatari Schools: Possible Impact on Student Achievement - Ahmad A. El-Emadi (22415620) (2019)
In Qatar’s gender-segregated public schools, female students outperform male students in international science tests such as PISA and TIMMS. In contrast to the international trend for top performing countries, however, female students report lower levels of interest in science-based careers than males. One possible factor that may contribute to this discrepancy is the difference in teaching styles between female teachers and their male counterparts. In this paper we focus on results obtained from 105 classroom observations (39 males and 66 females) selected from 50 different public schools as part of two independent research projects to study the motivation factors and attitudes toward and interest in science among Qatari students. In addition, 40 semi-structured interviews of students, teachers and administrators were conducted. The observations were guided using an adopted Reformed Teaching Observation Protocol (RTOP) evaluation rubric consisting of 13 teaching traits which provides a standardized mean for detecting the degree to which science classroom instruction is reformed through a focus on Lesson Design, Content, Pedagogic Knowledge and classroom culture. Female teachers provided better delivery during theory classes, whereas male teachers demonstrated better performance in laboratory-based classes. Other Information Published in: EURASIA Journal of Mathematics, Science and Technology Education License: https://creativecommons.org/licenses/by/4.0/   See article on publisher's website: https://dx.doi.org/10.29333/ejmste/109236 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.